Celecoxib enhances radiation response of secondary bone tumors of a human non-small cell lung cancer via antiangiogenesis in vivo - Klenke, Frank Michael; Abdollahi, Amir; Bischof, Marc; Gebhard, Martha-Maria; Ewerbeck, Volker; Huber, Peter E.; Sckell, Axel (Strahlentherapie und Onkologie, 2011)
Cyclooxygenase-2 (COX-2) inhibitors mediate a systemic antitumor activity via antiangiogenesis and seem to enhancethe response of primary tumors to radiation. Radiosensitizing effects of COX-2 inhibition have not been reported for bone metastases.Therefore, the aim of this study was the investigation of the radiosensitizing effects of the selective COX-2 inhibitorcelecoxib in secondary bone tumors of a non-small cell lung carcinoma in vivo.